2018
DOI: 10.1111/jeb.13390
|View full text |Cite
|
Sign up to set email alerts
|

Crickets increase sexual signalling and sperm protection but live shorter in the presence of rivals

Abstract: The sociosexual environment animals experience through their life can shape the evolution of key life history traits, including longevity. Male–male competition, for instance, may influence the resources allocated to traits involved in male reproductive success. Here, I test whether lifelong exposure to a competitor male influences male investment in pre‐ and post‐copulatory sexual traits (calling effort and sperm quality) and how this affected the oxidative status and longevity of male field crickets (Gryllus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Accordingly, studies have shown that reproductive effort can increase oxidative damage and decrease antioxidant capacity in a range of animal species (Christe et al, 2012; Sawecki et al, 2019; Sharick et al, 2015; Stier et al, 2012), and that oxidative stress can negatively affect survival or lifespan (Archer et al, 2013; Bize et al, 2008). In many animals species, social dominance is associated with breeding, and similarly, there is cumulative evidence that social dominance results in an oxidative cost, especially when high dominance is linked to intense agonistic interactions (Beaulieu et al, 2014; Border et al, 2019; van de Crommenacker et al, 2011) and/or increased reproductive effort (Cram et al, 2015; Noguera, 2019; Silva et al, 2018). At the same time, there are also several studies suggesting there is no oxidative cost of social dominance and/or reproduction and that breeding may even reduce oxidative stress (Blount et al, 2016; Costantini et al, 2014; Garratt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, studies have shown that reproductive effort can increase oxidative damage and decrease antioxidant capacity in a range of animal species (Christe et al, 2012; Sawecki et al, 2019; Sharick et al, 2015; Stier et al, 2012), and that oxidative stress can negatively affect survival or lifespan (Archer et al, 2013; Bize et al, 2008). In many animals species, social dominance is associated with breeding, and similarly, there is cumulative evidence that social dominance results in an oxidative cost, especially when high dominance is linked to intense agonistic interactions (Beaulieu et al, 2014; Border et al, 2019; van de Crommenacker et al, 2011) and/or increased reproductive effort (Cram et al, 2015; Noguera, 2019; Silva et al, 2018). At the same time, there are also several studies suggesting there is no oxidative cost of social dominance and/or reproduction and that breeding may even reduce oxidative stress (Blount et al, 2016; Costantini et al, 2014; Garratt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is common for males to put more effort into singing (greater singing effort or higher duty cycle) if they can hear rival males (e.g. Anichini et al, 2018;Callander et al, 2013;Mhatre and Balakrishnan, 2006;Morris et al, 2002;Noguera, 2019;. Males of one Mecapoda bush-cricket species simply start singing as soon as a rival does (Krobath et al, 2017).…”
Section: Plasticity In Male Behaviourmentioning
confidence: 99%
“…Previous studies have shown that male calling effort is strongly affected by the social environment, whether that be developmental plasticity caused by the perception of future competition at the juvenile stage (Kasumovic et al 2012;Kasumovic et al 2013), flexibility caused by recent or current exposure to rival males (Callander et al 2013;Noguera 2018), or current access to potential mates (Houslay et al 2017). Here we show that males also exhibit an increase in calling effort when exposed directly to another male.…”
Section: Exposure To Rival Males Increases Calling Effortmentioning
confidence: 99%
“…The same study demonstrated that signalling investment is highly responsive to the availability of a potential mate: males are more likely to signal, and signal for longer, if a female is present relative to when absent. In related species of crickets, the recent or current presence of rival males at adulthood can increase calling effort (Callander et al 2013;Noguera 2018), suggesting plasticity of signalling behaviour based on perceived competition. Manipulations of the juvenile social environment have also indicated that crickets can perceive future competition rates and adjust investment in reproductive tissues (Bailey et al 2010) and agespecific calling effort (Kasumovic et al 2013) accordingly.…”
Section: Introductionmentioning
confidence: 99%